Beliefs and attitudes of professionals about marital violence: studies with health professionals, policemen and teachers. - Machado, Carla (2009)
This article presents a set of three research projects that aimed to characterize the beliefs about marital violence of the professionals most directly implied in the response and prevention of this problem. A research questionnaire that evaluates beliefs about marital violence was administered to a sample of 226 health professionals, 85 law enforcement agents and 280 teachers. On the global results show a tendency to moderate disagreement with beliefs that legitimize this form of abuse. Some myths, however, persist in these samples, namely those related to the privacy of the problem, its rarity and attribution to external causes. Male and older subjects show, in general, higher levels of violence legitimization.